Sedition a novel - Grant, Katharine (Henry Holt and Company, 2014)
The setting: London, 1794. The problem: Four nouveau riche fathers with five marriageable daughters. The plan: The young women will learn to play the piano, give a concert for young Englishmen who have titles but no fortunes, and will marry very well indeed. The complications: The lascivious (and French) piano teacher; the piano maker's jealous (and musically gifted) daughter; the one of these marriageable daughters with a mating plan of her own. While it might be a truth universally acknowledged that a man in possession of a title and no money must be in want of a fortune, what does a sexually awakened young woman want? In her wickedly alluring romp through the late-Georgian London, Italian piano making, and tightly-fitted Polonaise gowns, Katharine Grant has written a startling and provocative debut.